2003
DOI: 10.1002/ldr.546
|View full text |Cite
|
Sign up to set email alerts
|

Potentials and constraints of the farmer‐to‐farmer programme for environmental protection in Nicaragua

Abstract: The natural environment in Nicaragua has been damaged by rural development policies geared for the export of cash crops, by uneven land distribution and the near absence of concerns about the environmental effects of the prevailing model of development. The demands made by market forces for the export of primary materials have been reasons for land degradation in the big farms, and the need to survive a poverty stricken existence has forced the peasantry to damage the marginal and fragile land they worked. Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
(10 reference statements)
1
14
0
Order By: Relevance
“…However, travel distances reduced as they acquired experience because farmers nearby began to seek their services as their ability became apparent. Our findings agreed with those of Braun and Hocde (2000) and Hawkesworth et al (2003), who reported that credibility and ability of farmer trainers needs to be tested and seen by farmers in order for them successfully to share their knowledge and experiences with others.…”
Section: Selection Of Farmer Trainerssupporting
confidence: 95%
“…However, travel distances reduced as they acquired experience because farmers nearby began to seek their services as their ability became apparent. Our findings agreed with those of Braun and Hocde (2000) and Hawkesworth et al (2003), who reported that credibility and ability of farmer trainers needs to be tested and seen by farmers in order for them successfully to share their knowledge and experiences with others.…”
Section: Selection Of Farmer Trainerssupporting
confidence: 95%
“…This information is conducive to the development of chiral pharmaceuticals and pesticides with a short half-life, high bioactivity, and low ecological toxicity. Importantly, the chiral ethiprole enantiomers exert dramatically different influences on soil microbial community structures and ecological succession in agroecosystems (Hawkesworth & García Pérez, 2003). Therefore, we propose that the enantioselective behavior and resultant ecotoxicology of chiral pesticides need to be considered in pesticide registration before the application of a chiral pesticide in agricultural systems.…”
Section: Enantioselectivity In Microbial Assemblymentioning
confidence: 99%
“…At the center of this approach are farmer trainers, known by many different names in different countries and projects. In Nicaragua, the farmer trainers are known as promoters (Hawkensworth and Garcia Perez 2003) while the International Centre of Insect Physiology and Ecology in Kenya calls them farmer teachers (Amudavi et al 2009). In Burkina Faso, farmer trainers are known as farmer advisors (Lenoir 2009) while in Peru they are known as farmer extension agents (Kamayoq) (Hellin and Dixon 2008).…”
Section: The Volunteer Farmer-trainer Approachmentioning
confidence: 99%